2022
DOI: 10.1002/gj.4378
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of intraplate magmatism and subduction magmatism during the formation of Nagaland–Manipur Ophiolites, Indo–Myanmar Orogenic Belt, north‐east India

Abstract: Mafic extrusive rocks (basalts) and intrusive rocks (gabbros) from the Nagaland–Manipur Ophiolite (NMO) of the Indo–Myanmar Orogenic Belt (IMOB), north‐east India, are investigated to understand their magmatic evolution in diverse tectonic environments. Basalts are distinguished into two types: basalt‐I and basalt‐II. Basalt‐I type shows the sub‐alkaline character with Nb/Y < 0.50, low Nb/Th (2.36–7.94), and low to moderate La/Sm (1.00–4.12) indicating derivation from a slightly enriched mantle source and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The NMO is highly tectonized and dismembered, the westerly convex arcuate belt of ~200 km length extending from north‐east of Chokla in Nagaland to Moreh in Manipur, with an average width of ~15 km (Chattopadhyay, Venkataramana, Roy, Bhattacharyya, & Ghosh, 1983). Ophiolites in the NMO (Figure 1c) have mainly formed in the SSZ setting but contain rocks of varied affinities, such as MORB, OIB, and IAT (Abdullah, Misra, & Ghosh, 2018; Imtisunep et al, 2022; Khogenkumar et al, 2016, 2020; Sengupta et al, 1989; Singh, 2013; Singh et al, 2013; Singh, Nayak, et al, 2017; Zaccarini et al, 2016). These ophiolites have undergone different phases of tectonism, metamorphism, magmatism, and metallogenic events that mimic the Himalayan Orogeny (Ghose, Agrawal, & Chatterjee, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
“…The NMO is highly tectonized and dismembered, the westerly convex arcuate belt of ~200 km length extending from north‐east of Chokla in Nagaland to Moreh in Manipur, with an average width of ~15 km (Chattopadhyay, Venkataramana, Roy, Bhattacharyya, & Ghosh, 1983). Ophiolites in the NMO (Figure 1c) have mainly formed in the SSZ setting but contain rocks of varied affinities, such as MORB, OIB, and IAT (Abdullah, Misra, & Ghosh, 2018; Imtisunep et al, 2022; Khogenkumar et al, 2016, 2020; Sengupta et al, 1989; Singh, 2013; Singh et al, 2013; Singh, Nayak, et al, 2017; Zaccarini et al, 2016). These ophiolites have undergone different phases of tectonism, metamorphism, magmatism, and metallogenic events that mimic the Himalayan Orogeny (Ghose, Agrawal, & Chatterjee, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
“…It is reported that the rocks of the MOMZ formed during forearc‐backarc magmatism in a supra‐subduction zone, probably when the Indian Plate was subducting underneath the Myanmar Plate (Ao & Bhowmik, 2014; Chaubey et al, 2022; Kingson et al, 2019; Singh et al, 2016; Singh et al, 2021; Zaccarini et al, 2016). However, it is also proposed that this ophiolite was formed in a mid‐oceanic ridge spreading center (Ningthoujam et al, 2012; Singh, 2009; Zaccarini et al, 2016), or plume‐ridge interaction as one event and subduction magmatism as another event (Imtisunep et al, 2022; Khogenkumar et al, 2016, 2020). Although many studies have reported the formation age of this ophiolite, there is general agreement that the upper limit age probably extends up to the Eocene, while the lower age limit is probably Upper Jurassic.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The ophiolite sequences occurring all along the Tuting‐Tidding Suture Zone, which runs east of the Siang Antiform have been considered as the south‐eastern extension of the ITSZ (Dutt, Singh, Oinam, & Srivastava, 2021; Dutt, Singh, Srivastava, & Oinam, 2021; Dutt, Singh, Srivastava, Oinam, & Bikramaditya, 2021; Singh et al, 2021; Singh & Singh, 2011, 2013). The suture zone further extends south to the IMOB and the Andaman‐Nicobar Island Arc (Chaubey et al, 2022; Imtisunep et al, 2022; Khogenkumar et al, 2016, 2021; Premi et al, 2022; Singh, 2009; Singh, 2013; Singh et al, 2012; Singh et al, 2013; Singh, Nayak, et al, 2017).…”
Section: General Geologymentioning
confidence: 99%